Thrombospondin-1 and CD47 Regulation of Cardiac, Pulmonary and Vascular Responses in Health and Disease - Rogers, Natasha M. (2014)
Cardiovascular homeostasis and health is maintained through the balanced interactions of cardiac generated blood flow and cross-talk between the cellular components that comprise blood vessels. Central to this cross-talk is endothelial generated nitric oxide (NO) that stimulates relaxation of the contractile vascular smooth muscle (VSMC) layer of blood vessels. In cardiovascular disease this balanced interaction is disrupted and NO signaling lost. Work over the last several years indicates regulation of NO is much more complex than previously believed. It is now apparent the secreted protein thrombospondin-1 (TSP1), that is upregulated in cardiovascular disease and animal models of the same, on activating cell surface receptor CD47, redundantly inhibits NO production and NO signaling. This inhibitory event has implications for baseline and disease-related responses mediated by NO. Further work has identified that TSP1-CD47 signaling stimulates enzymatic reactive oxygen species (ROS) production to further limit blood flow and promote vascular disease. Herein consideration is given to the most recent discoveries in this regard which identify the TSP1-CD47 axis as a major proximate governor of cardiovascular health.